Experimental study of care in mental patients treated with Cardiazol - Fernández Quintana, Armando (1939)
Since the discovery of treatment of schizophrenia by injections (intravenous) Cardiazol - treatment to be extended to other forms of mental illness - there have been countless studies that approach the issue from different points of view.